Peningkatan Kompetensi Penyusunan Bahan Ajar Bahasa Indonesia bagi Penutur Asing Berbasis Budaya dan Tradisi Jawa Tengah bagi Dosen Thammasat University Thailand - Kundharu Saddhono; Ani Rakhmawati; Muhammad Rohmadi; Maulana Danar Maaliki H (Institut Teknologi dan Bisnis Semarang, 2024)
Indonesian is experiencing very rapid development, not only in Indonesia but also abroad. This is proven by many foreign speakers who are interested in learning Indonesian for Foreign Speakers. One of the countries in the ASEAN region that holds BIPA learning is Thailand. The general aim of PKMI is to develop teaching materials based on local Central Javanese cultural wisdom for BIPA teachers at Thammasat University Thailand in the BIPA learning program. The main problem with BIPA teaching in Thailand is that the lack of textbooks, teaching materials and other supporting resources can be an obstacle in providing effective teaching and also providing quality teachers, especially those who have a background in teaching Indonesian as a Foreign Language. In essence, for learning to run well, interesting and innovative learning media is needed. This requires finding a good solution so that appropriate assistance is needed. The specific objectives are to describe the current condition of BIPA teaching materials, explore the need for developing BIPA teaching materials based on the local wisdom of Central Javanese culture and implement teaching materials containing local cultural wisdom of Central Java that can be used at Thammasat University, Thailand which are made by BIPA teachers with guidance from the PKMI UNS team. The location of this PKMI is at Thammasat University. The PKMI implementation method is planned in 3 major stages, each of which has a different form of activity. The preparation stage relates to things that need to be prepared in order to implement this PKMI. The implementation stage is the core of this PKMI which will be carried out at Thammasat University, Thailand. The evaluation stage is the final stage of this PKMI which will be carried out by the PKMI Team regarding an assessment of what BIPA teachers at Thammasat University, Thailand have done before and after training and guidance as well as developing BIPA teaching materials based on Central Javanese culture.